Screen time, physical activity and cardiovascular risk factors in adolescents - Gabriel Gustavo Bergmann; Rafael Miranda Tassitano; Mauren Lúcia de Araújo Bergmann; Maria Cecília Marinho Tenório; Jorge Mota (Revista Brasileira de Atividade Física e Saúde)
The aim of this study was to examine the independent and combined associations of physical activity and different types of screen time in cardiovascular disease risk factors in adolescents. e sample was comprised for 1,045 adolescents (51.7% female) aged 11-17 years old randomly selected. Screen time was considered by the self-related electronic devices such as time watching TV, using computer (PC) and playing videogame (VG). Physical activity was estimated by the number of steps per day (steps/ day) measured by pedometers. Cardiovascular risk factors were sum of triceps and subscapular skin- folds (∑SF), total cholesterol (TC) and blood pressure (BP). Predictors and outcome variables were dichotomized using standardized cut o points. Categories of steps/day and different types of screen time were cross tabulated to the combined analyses. A set of sociodemographic variables was used as confounders. To test the independent and combined associations Chi-square tests (unadjusted) and binary logistic regression (adjusted) were used. TV time was directly and independently associated to ∑SF in females and to TC in males. Steps/day was inversely and independently associated to TC and to BP (not in female). Overall, combined analyses showed that adolescents who did not meet recommendations of steps/day and exposure an excessive screen time are more likely to present cardiovascular risk factor. Public health programs to increase physical activity and reduce screen time, especially TV time, should be developed to improve and prevent cardiovascular health in adolescents.